Efeito da adição de cúrcuma (Curcuma longa l.) na manteiga caprina clarificada sobre parâmetros comportamentais e bioquímicos em ratos adolescentes - Costa, Ana Carolina dos Santos (2020)
Turmeric is a food with functional potential with several metabolic and behavioral effects, such as goat fat. In order to evaluate the effect of these two foods in a combined and isolated way, the objective of this research was to evaluate the effects of the consumption of goat clarified butter, added with turmeric, on behavioral, murinometric, biochemical and lipid peroxidation parameters in adolescent rats with 35 days of life. The animals were randomly divided into four groups: Control (CONT), n = 9 - distilled water; Turmeric (CM), n = 10 - 60 mg of turmeric / kg of animal weight; Caprine Butter (BT), n = 10 - 2,000 mg of goat butter / kg of weight; Turmeric Butter (BTCM), n = 10 - 2,000 mg / kg of animal weight, 3% (60 mg / kg) of turmeric, added to butter. The animals received the treatment by gavage for 28 days, the day after the end of the treatment, short and long term memory parameters were evaluated, using the Object Recognition Task (ORT), and the spatial memory in the Morris Water Labyrinth. . Subsequently, anxiety tests were performed in the open field, elevated plus maze (EPM) and light-dark box apparatus. At the end of the behavioral tests, the animals were anesthetized and evaluated in relation to body weight, length, body mass index, waist and chest circumference, and then they were euthanized. Total fat, organ weight (liver and brain), biochemical profile (Glucose, Total cholesterol, TGC, HDL, LDL, ALT, AST), MDA (liver and brain) and the content of liver and brain fatty acids were analyzed. Weight and food consumption were assessed during the experiment. Data were analyzed using analysis of variance followed by Tukey and Holm Sidak, being considered significant when p <0,05. There were no changes in murinometric parameters, but there was a difference in liver parameters with a reduction in the percentage of liver fat in CM and BT in relation to CONT and BTCM (p <0,05) and a reduction in AST in the experimental groups; in the biochemical markers CM, it reduced glucose, CT, LDL-c and TGC and increased HDL-c; BT decreased CT, LDL-c and triglyceride and BTCM reduced CT, LDL-c and HDL-c, both treatments in relation to CONT (p <0,05); hepatic lipid peroxidation increased in the experimental groups (p <0,05). The result of the fatty acid profile of the CM liver showed a reduction in the SFA content; BT and BTCM increased the content and MUFA; PUFA increased in experimental groups. Short-term and long-term memory decreased by BTMC and CM, respectively (p >0,05). Aquatic maze all treatments showed improvement in spatial memory in relation to CONT (p <0,05). The behavior related to anxiety, BTCM showed better performance in the open field, EPM and light and dark box apparatus, and reduction in the level of cerebral MDA. The fatty acid profile of the brain reduced SFA and increased MUFA in BTCM, in relation to the other treatments, PUFA showed a slight increase in BTCM, in relation to CONT. The results indicate a potential improvement in the liver and biochemical markers of animals treated with turmeric and butter in isolated ways. Positive effects were observed in non-associative and spatial memory, as well as in the potentiation of anxiolytic-like behavior and in the decrease in the level of lipid peroxidation in the brain of animals treated with goat butter added with turmeric.